Digital technology in dental education during COVID-19 pandemic : worldwide experience of professors and students = Tecnología digital en la educación odontológica durante la pandemia por COVID-19 : experiencia mundial de profesoresy estudiantes - Dantas Costa, Eliana; Moura Brasil, Danieli; Machado Santaella, Gustavo; Cascante Sequeira, Deivi Antonio 1983-; Saverio Ludovichetti, Francesco (2021)
The objective of this study was to assess the use and experience with digital communication tools among dentistry professors and students to adapt to distance learning during the Covid-19 pandemic. Nine hundread and ninety five participants (479 dentistry professors and 516 students) from countries in North America, Latin America, Brazil, Europe, Asia, Oceania, and the Middle East answered a questionnaire about motivation/stress/anxiety; practice with digital technologies; synchronous/asynchronous communication technologies (difficulties/benefits), and which ones would they prefer using when returning to college. Data were analyzed by the Chi-square test and Fisher's exact (α=0.05). Motivation was more affected among the female professors, male students, and Brazilians (p<0.05). Concern about the academic future, was higher among female students, up to 30 years old, from Latin America and Brazil, and lower for European professors (p<0.05). Anxiety and stress were higher for undergraduate students up to 20 years old from Latin America and Brazil (p<0.05). European professors used more synchronous videoconferencing services for lectures/questions, while Brazilians used more text messaging applications for answering questions (p<0.05). Latin American professors used more surveys for evaluation (p<0.05). Brazilian professors indicated that they would use "online meetings" and "survey administration services" when returning to face-to-face activities and European professors/students would use "email" (p<0.05). Professors from Asia/Oceania/Middle East and professors/students from Brazil indicated "remote activities were important for students not to be inactive" (p<0.05). Efforts were made to adapt Dentistry's teaching to distance learning during the COVID-19 pandemic. However, the technologies used for this, feelings, and experiences differed between professors and students.
El objetivo de este estudio fue evaluar el uso y la experiencia con herramientas de comunicación digital entre profesores y estudiantes de odontología para adaptarse al aprendizaje a distancia durante la pandemia Covid-19. Novecientos noventa y cinco participantes (479 profesores y 516 estudiantes de odontología) de países de diferentes regiones de América del Norte, América Latina, Brasil, Europa, Asia, Oceanía y Oriente Medio respondieron un cuestionario sobre motivación/estrés/ansiedad; práctica con tecnologías digitales; tecnologías de comunicación sincrónicas/asincrónicas (dificultades/beneficios), y cuáles continuarían usando al regresar a la universidad. Los datos se analizaron mediante las pruebas Chi-cuadrado y exacta de Fisher (α=0,05). La motivación se vio más afectada entre las profesoras, estudiantes y brasileños (p<0,05). La preocupación por el futuro académico fue mayor entre las estudiantes, hasta los 30 años, de América Latina y Brasil, y menor para el profesorado europeo (p<0,05). El estrés fue mayor para el estudiantado de pregrado de Latinoamérica y Brasil hasta los 20 años (p<0.05). El profesorado europeo utilizó más servicios de videoconferencia sincrónica para clases y consultas, mientras que el brasileño utilizó más aplicaciones de mensajería de texto para consultas (p<0,05). El profesorado latinoamericano utilizó más encuestas para evaluación (p<0.05). El profesorado brasileño indicó que utilizaría "reuniones en línea" y "servicios de encuestas" cuando regresaran a la presencialidad, mientras que el profesorado/estudiantado europeo utilizaría "correo electrónico" (p<0,05). El profesorado de Asia/Oceanía/Medio Oriente y profesorado/estudiantado de Brasil indicó que "las actividades remotas eran importantes para que el estudiantado no estuviera inactivo" (p<0,05). Se relizaron esfuerzos para adaptar la enseñanza de la Odontología al aprendizaje a distancia durante...
En revista Odóvtos, vol. 23, no.3 (septiembre-diciembre 2021)
Descripción basada en el contenido visto el 14 de noviembre, 2024
También disponible en formato HTML y EPUB